PENERAPAN TEKNIK UNTUNG RUGI DALAM MENINGKATKAN SELF ESTEEM MELALUI LAYANAN INFORMASI SISWA KELAS VIII DI SMP N 8 KOTA JAMBI - Aqmi, Maya Shirol; Sutja, Akmal; Yaksa, Rully Andi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Self-esteem is one of the basic human needs in carrying out life, which can provide a feeling of success and usefulness even though the individual has weaknesses and even experiences a failure in life. This study aims for an improvement, changes related to the problem of self-esteem (self esteem) have increased with the profit and loss technique in information services. This profit and loss technique is very effective in helping students to think critically by considering the plus-minus or profit and loss aspects of knowing and not knowing self-esteem, and helping to justify their views and problems regarding self-esteem. This type of research is PTL (Service Action Research), which specifically relates directly to counseling guidance. This study consists of 3 cycles, consisting of Planning, Implementation, Evaluation, and Reflection, using quantitative and qualitative research methods. Based on the results obtained from each cycle implementation, cycle (I) increased students' self esteem by 39.5%, then in the implementation of cycle (2) increased students' self esteem increased by 45.8%, then in the implementation of cycle (3) increased students' self esteem increased by 81%. Based on this, it can be concluded that the results of the cycle are categorized as good in the third cycle, which is the third cycle. It is hoped that this research can be obtained as a reference to the development of the knowledge of other parties to be used as further research in seeking development and study of problems that are overall more detailed in helping students and society.